Masculinity and veganism: the effect of linking vegan dishes with masculinity on men's attitudes toward vegan food - Scholz, Alma Elisabeth; Lenhart, Jan (Frontiers in Communication, 2023)
Vegetarian or vegan diets are not yet popular with most men, though they are beneficial for both health and the environment. Men’s low preference for such diets might stem from the prevalent association of meat with masculinity and of veganism with femininity. Accordingly, linking vegan nutrition to masculinity might help to develop a favorable attitude towards plant-based diets in men. Accordingly, the present study examined the effects of a masculine framing of vegan dishes on men’s attitudes toward vegan food and veganism. In addition, we explored whether adherence to traditional forms of masculinity might increase the effects of masculine framing. To do so, we conducted an online experiment with a 2 (man vs. woman) x 2 (conventional vs. masculine framing) design, in which 593 adults participated. We measured participants’ attitudes towards vegan dishes (dish ratings, hunger ratings) and veganism (veganism ratings, vegan scenarios ratings), the perceived suitability of the dishes for men and women as well as men’s identification with masculinity. We found that a masculine framing of vegan dishes influenced the gender association of the dishes, weakening the link to femininity. However, masculine framing did not influence men’s or women’s attitudes towards the presented vegan dishes or veganism in general. Although the extent to which men identified with new forms of masculinity correlated positively with favorable attitudes towards veganism, new masculinity identification did – with an exception for the rating of the presented dishes – not moderate the effect of the experimental condition.